Hubungan Beban Kerja Dan Kepuasan Kerja dengan Kinerja Karyawan di Instalasi Rekam Medis Rumah Sakit Mata "Dr.YAP" Yogyakarta - Ningsih, Kori Puspita, Prof. Dr. Bhisma Murti, MPH., M.Sc., PhD, Sugeng, A.Md., SKM (2013)
Assessment of individual performance was very benefical to growth dynamics of the organization a whole, through the asssessment, it can be known about condition actual performance of employee. The objective of his study to identify relationship workload and job satisfaction with work performance in "Dr.Yap" Eye's Hospital Yogyakarta. This research used observation survey, it is an analitic descriptive study with qualitative approach and supported by quantitative approach for data collection and cross sectional research design. Subject research were 8 employee's in Medical Record Instalation. Object research was diaries document of activities employees from arrival until returned, Standar Operating Procedures and recapitulation absenteeism. Data were collected were indepth interview, Focus Group Discusion (FGD), documentation and observation. The result from this study are workload that stimultaneously have relationship with work performance. Greather workload diminishing performance. Job satisfaction that stimultaneously have relationship with work performance. Higher job satisfaction increase work performance.